Best practices for internal Shariah governance framework : lessons from Malaysian Islamic banks - Rosli Abdul Aziz; Aisyah Abdul-Rahman; Ruzian Markom (Penerbit Universiti Kebangsaan Malaysia, 2019)
Comprehensive compliance to Shariah principles ensure confidence among stakeholders and strong credentials for the banking institutions. The Shariah Governance Framework (SGF) was introduced by the BNM in 2010 to safeguard Islamic financial institutions’ Shariah compliancy. Non-compliancy to SGF will pose risks to the banks and cause instability in the financial industry. This study explores the implementation of the internal SGF in selected Islamic banks. Document reviews and interviews were conducted to analyse the SGF documentations and practices. The banks’ practices are compared to the Guidelines on the Governance of Shariah Committee (GGSC) 2005 and the SGF 2010. Roles of major Shariah committees were reviewed with regard to the banks’ internal SGF compliancy to the SGF 2010. The findings indicate that the Islamic banks are generally compliant to the SGF 2010 provisions. The banks’ implementation of major Shariah organs has facilitated regulators in monitoring and mitigating Shariah non-compliancy events or risks. The most challenging issue faced by the Shariah audit team is limited resources in terms of on-the job work experience or Shariah knowledge. Thus, it is essential for Islamic banks to enhance their internal SGF within the scope of the SGF 2010 and collaborate with training agencies or higher education-related parties in addressing shortage of skilled manpower.